The predictive power of post-colonial ideologies: Historical Negation and Symbolic Exclusion undermine support for resource-based bicultural policies. (January 2018) - Newton, Helena J.; Sibley, Chris G.; Osborne, Danny
Abstract: Past research predicting political attitudes from belief systems has predominantly focused on general ideologies that neglect the specific socio-historical contexts in which these attitudes develop. We address this limitation by proposing that bicultural-related political attitudes in post-colonial nations are best predicted by ideologies specific to the post-colonial context. Two post-colonial ideologies previously demonstrated to predict political attitudes are the belief (a) that colonial history is irrelevant to contemporary inequalities (Historical Negation) and (b) that Indigenous cultures are irrelevant to national identity (Symbolic Exclusion). As hypothesized, results from a national probability sample of adult Pākehā (i.e., New Zealand Europeans; N = 15, 607) showed that Historical Negation and Symbolic Exclusion uniquely predicted opposition to four resource-based bicultural policies after adjusting for a range of general ideologies and demographic characteristics. These findings demonstrate the need to examine ideologies that develop within a particular socio-historical context when predicting political attitudes in post-colonial nations.